Wody Polskie jako regulator rynku wodno-kanalizacyjnego - Górka, Marta (Wydawnictwo Uniwersytetu Wrocławskiego, 2022)
As a result of the amendment to the Water Law Act, a completely new institution was established, responsible for the functioning of water management in our country — The State Water Holding Polish Waters. The reason for the creation of Polish Waters was centralizing most of the tasks and competences related to water management in the country within one institution. In addition, Polish Waters obtained the status of a regulatory authority in the water and sewage market whose most important tasks include the approval of water and legal tariffs. The aim of the article is to investigate the impact of Polish Waters on the functioning of the water and sewage market and to analyze the mechanisms influencing the behavior of regulated entities in terms of their effectiveness. Due tothe emergence of a new regulatory authority in the structure of the Polish administration, doubts about the scope of its competences are beginning to appear more and more often. Unfortunately, they are not unequivocally resolved by the applicable regulations. All these issues deserve an in-depth analysis which will be presented in this article.
Keywords: Polish Waters; regulation; regulatory authority; water and sewage management; water and sewage tariff